1992
DOI: 10.1007/bf02446177
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic processing: using microstructures to solve a hitherto intractable neurobiological problem

Abstract: In vivo, intracellular recordings of mammalian brain stem motoneurones, followed by peroxidase staining and tridimensional reconstruction, suggest that the shape of the dendritic tree plays an important role in the processing of neural information. To test this hypothesis attempts were made to guide, in culture, the growth of neuritic branches of neurones dissociated from the hypoglossal nucleus of rat brain stem. This was performed using topographical and adhesive microstructures which were designed to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Microfabricated surfaces with microgrooves of various depths, widths and spacings have demonstrated that initial axon growth of neurons isolated from different species and brain regions is directed by topographic cues (Ternaux et al 1992, Nagata et al 1993, Rajnicek et al 1997. These cues differ for different cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microfabricated surfaces with microgrooves of various depths, widths and spacings have demonstrated that initial axon growth of neurons isolated from different species and brain regions is directed by topographic cues (Ternaux et al 1992, Nagata et al 1993, Rajnicek et al 1997. These cues differ for different cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen increasing use of micro-fabrication and nano-fabrication technology in the study and practical applications of cell patterning. [6][7][8] While patterned substrates are primarily used for cell culturing, they are also being applied to experiments conducted in vivo, especially for the study of tissue rejection phenomenon associated with medical implants and the overall effectiveness of such structures. Conventional photolithography, contact printing and lift-off approaches, once used only for producing microelectronic devices, are now being employed for the complex chemical patterning of surfaces for a number of applications connected to cell attachment.…”
Section: The Neuron-substrate Interfacementioning
confidence: 99%
“…[6][7][8] While patterned substrates are primarily used for cell culturing, they are also being applied to experiments conducted in vivo, especially for the study of tissue rejection phenomenon associated with medical implants and the overall effectiveness of such structures. In earlier work, various forms of surface roughening and coatings have been used with respect to dental and orthopedic implants.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies include the work of Fromherz et al on using field-effect transistors to sense action potentials (25) and others on the fabrication of microelectrodes (18,21,57). Several groups have used photolithography pattern the chemical or physical properties of cell-culture substrates to control the patterns of adhesion or migration of cells (17,20,32,66). The work of Fodor et al combining photolithographic chemical synthesis with optical sensing (24) is also worth reading about.…”
Section: Introductionmentioning
confidence: 97%